2024
DOI: 10.3390/su16103923
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation of the Density Effect on the Macroscopic Transport Process of Tracer in the Ruhrstahl–Heraeus (RH) Vacuum Degasser

Zhibo Xu,
Xin Ouyang,
Chao Chen
et al.

Abstract: Silicon steel (electrical steel) has been used in electric motors that are important components in sustainable new energy Electrical Vehicles (EVs). The Ruhrstahl–Heraeus process is commonly used in the refining process of silicon steel. The refining effect inside the RH degasser is closely related to the flow and mixing of molten steel. In this study, a 260 t RH was used as the prototype, and the transport process of the passive scalar tracer (virtual tracer) and salt tracer (considering density effect) was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…The effect of salt solution tracers on fluid flow in batch reactors, for example, vacuum refining ladle furnaces [68][69][70] and gas-stirred ladles [71][72][73], have also been studied. For gas-stirred ladles, Chen et al [71] demonstrated that increasing the quantity of the tracer reduces the mixing time.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of salt solution tracers on fluid flow in batch reactors, for example, vacuum refining ladle furnaces [68][69][70] and gas-stirred ladles [71][72][73], have also been studied. For gas-stirred ladles, Chen et al [71] demonstrated that increasing the quantity of the tracer reduces the mixing time.…”
Section: Introductionmentioning
confidence: 99%